The Usefulness of the Leuprolide Stimulation Test as a Diagnostic Method of Idiopathic Central Precocious Puberty in Girls - Carretto, F.; Salinas-Vert, I.; Granada-Yvern, M. L.; Murillo-Vallés, M.; Gómez-Gómez, C.; Puig-Domingo, M.; Bel, J. (Hormone and Metabolic Research, 2014)
Central precocious puberty (CPP) diagnosis is based on clinical evaluation, but hormonal evaluation is crucial. The aim of the study was to evaluate the usefulness of the leuprolide stimulation test for diagnosis of idiopathic CPP. Sixty-one girls, aged 5–8 years, were evaluated retrospectively for premature breast development. According to clinical evolution, 28 had progressive puberty and 33 nonprogressive puberty. All underwent a leuprolide stimulation test. Cutoff points, sensitivity, and specificity for gonadotropins and estradiol were determined by receiver operating characteristic (ROC) curves. Cutoff points for CPP were: baseline LH: > 0.1 mUI/l, FSH: > 2.3 mUI/l, LH/FSH ratio: > 0.23, estradiol: > 12 pg/ml; and stimulated LH: > 5.5 mUI/l, LH/FSH ratio: > 0.24, estradiol: > 79.67 pg/ml. The best diagnostic efficiency for progressive puberty were stimulated LH/FSH ratio (sensitivity: 100%, specificity 94%) followed by stimulated LH (sensitivity: 93%, specificity: 100%). Stimulated LH/FSH ratio and LH resulted in the most useful parameters for the diagnosis of CPP. Stimulated estradiol did not add more information.
Keywords: central precocious puberty; leuprolide stimulation test; stimulated gonadotropin ratio